2016
DOI: 10.1101/047589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biphasic growth dynamics duringCaulobacter crescentusdivision

Abstract: 1 Cell size is specific to each species and impacts their ability to function. While 1 various phenomenological models for cell size regulation have been proposed, recent 2 work in bacteria have demonstrated an adder mechanism, in which a cell increments 3 its size by a constant amount between each division. However, the coupling between 4 cell size, shape and constriction, remain poorly understood. Here, we investigate size 5 control and the cell cycle dependence of bacterial growth, using multigenerational c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 25 publications
(14 reference statements)
2
17
0
Order By: Relevance
“…In many organisms like Caulobacter crescentus, size control is exerted in only a part of the cell cycle (36,37). More specifically, the cell cycle can be divided into two phases.…”
Section: Mixer Models For Size Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In many organisms like Caulobacter crescentus, size control is exerted in only a part of the cell cycle (36,37). More specifically, the cell cycle can be divided into two phases.…”
Section: Mixer Models For Size Controlmentioning
confidence: 99%
“…It is worth pointing out that the motivation behind separating the cell-size control into size-based (a) and timebased control ðf n Þ is to study the mixer model (such as that observed in C. crescentus) (36). Although there is some equivalence between the mixer model and the linear map considering a and D n as random variables, the latter is unable to distinguish the biphasic control (Supporting Material, Section S3).…”
Section: Mixer Models For Size Controlmentioning
confidence: 99%
“…A key question is how cells regulate their growth and timing of division to ensure that they do not get abnormally large (or small). This problem has ben referred to literature as size homeostasis and is a vigorous area of current experimental research in diverse organisms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We investigate if phenomenological models of cell size dynamics based on SHS can provide insights into the control mechanisms needed for size homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Two concepts have gained experimental support recently for regulating Caulobacter cell size and shape: (i) length homeostasis through “adder” or “mixer” mechanisms [101,102] and (ii) maintenance of a constant surface area to volume ratio under a given physiological condition [103,104]. The adder principle states that bacterial cells, including Caulobacter , achieve cell length homeostasis by growing a relatively constant amount prior to each cell division, regardless of length at birth [101].…”
Section: Shape Rules: Quantitative Principles Governing Cell Size Andmentioning
confidence: 99%
“…This idea is supported by time-lapse observation of the growth of thousands of cells, and contradicts earlier models such as the “sizer” model in which cells grow to a particular cell length threshold before dividing. A related model has been recently proposed, positing that Caulobacter cells grow according to a “mixer” mechanism (pre-print, [102]). Cells grow for a fixed fraction of their total cell cycle prior to initiating constriction (i.e.…”
Section: Shape Rules: Quantitative Principles Governing Cell Size Andmentioning
confidence: 99%